Mengembangkan Pembelajaran Interaktif Dan Menyenangkan Untuk Meningkatkan Skill Guru SDI PK Muhammadiyah Delanggu - Heni Susilowati; Ratnaningrum; Asnawi Hidayat (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2024)
The development of Technology and Information (IT) in the world of education is changing the way teachers convey knowledge to students. Teaching that has been carried out traditionally in one direction needs to be further developed with new learning methods that are interactive and interesting, more creative and participatory in order to increase student learning motivation. The aim of implementing PKM is to equip teachers to develop lesson materials in the form of IT-based interactive learning by utilizing the Canva and Microsof Excel applications. The activity was carried out at SDI PK Muhammadiyah Delanggu which was attended by 24 teachers by the PKM STIE STEKOM team. The training included making interactive quiz learning videos with the Canva application and processing student data with practical Microsoft Excel formulas. The results obtained from this activity were that all teacher participants gained skills and knowledge in developing learning media in the form of learning videos that were more interesting and interactive and completing administrative tasks could be done more quickly. Teachers succeeded in increasing their competency in using Canva and Microsof Excel as interactive learning media and completing assignments.